Tinjauan Siyasah Dusturiyah Tentang Peran Kementerian Agama Dalam Mengimplementasikan Program Moderasi Beragama (Studi Kasus di Kabupaten Bekasi) - Srikandi, Khodijah; Saebani, Beni Ahmad; Amin, Muhammad (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study examines the role of the Ministry of Religious Affairs of Bekasi Regency in implementing the religious moderation program using a siyasah dusturiyah approach in Bekasi Regency, a region known for its religious, cultural, and ethnic diversity. Due to this diversity, challenges arise in maintaining interreligious harmony and preventing conflicts. The Ministry's efforts in religious moderation include interfaith dialogue, inclusive education, and strengthening human resource capacity to foster social harmony. The objectives of this study are to analyze the role of the Ministry of Religious Affairs of Bekasi Regency in implementing the religious moderation program, identify challenges and evaluations in its implementation, and provide a siyasah dusturiyah review of the Ministry’s role in religious moderation. This research adopts an empirical juridical approach and a descriptive-analytical method. Primary data is collected through observations and interviews with officials from the Ministry of Religious Affairs in Bekasi Regency, while secondary data consists of official documents from the Ministry. The data is collected, classified, and interpreted using content analysis. From a siyasah dusturiyah perspective, the government’s duty and function are to establish policies that promote public welfare. This welfare includes ensuring social well-being, justice, peace, security, tolerance, and religious moderation. The findings conclude that the religious moderation program has positively impacted tolerance, leading to a more inclusive society and a decline in interfaith conflicts. However, a deeper public understanding of religious moderation is still needed through increased literacy and interactive interfaith dialogues. This study recommends strengthening collaboration between the Ministry of Religious Affairs, local governments, and society to address various obstacles hindering the religious moderation program. Strengthening these efforts will enhance the program’s effectiveness and success.